The effect of the built environment on spatial-temporal pattern of traffic congestion in a satellite city in emerging economies - Bao, Zhikang; Ng, S. Thomas; Yu, Gang; Zhang, Xiaoling; Ou, Yifu (Developments in the built environment, 2023)
Traffic congestion has been widely perceived as an inevitable byproduct in the process of global urbanization, leading to significant negative economic and environmental impacts. Existing studies have attached significant importance to revealing the interaction between traffic congestion patterns and built environment features in many metropolises with little attention, if any, paid to their counterparts of satellite cities (SC). For being aware that developing SCs has been a main trend to address many urban issues of metropolises in the rapid urbanization process of emerging economies, this study makes one of the first research attempts to investigate how traffic congestion temporally and spatially evolves with the built environment characterized by land use and transportation network features in Foshan, a typical SC of Guangzhou in China by using valuable hyperlocal travel data. The results show that while weekdays experience traffic peaks in both morning and evening, weekends or holidays generally only have the evening peak. The traffic congestion in Foshan during the pre-weekend is found much heavier compared with normal weekdays and weekends with a long-lasting effect possibly due to Foshan's role as a SC of Guangzhou. Additionally, the rising traffic congestion in a SC associated with company land use during the peak hours can be partly offset by the increasing supply of public transit, suggesting urban planners increase the density of public transit where there is a denser distribution of companies. This study provides new knowledge on travel behaviors in SCs in emerging economies, supplying urban governors with new insights for improving their traffic conditions generally. •The spatial-temporal traffic congestion-built environment relationship is explored.•This study makes one of the first such research attempts in a satellite city (SC).•The pre-weekend congestion may be much heavier with a long-lasting effect in a SC.•The positive impacts of public transit in alleviating traffic pressures are found.•Major congestion may occur along with the traffic line of the SC and the main city.